2013
DOI: 10.1053/j.ajkd.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Serum Alkaline Phosphatase in CKD Stages 3-4 in a Clinical Population

Abstract: Background Elevated total serum alkaline phosphatase (ALP) levels have been associated with mortality in the general population and in dialysis patients. Study Design Retrospective cohort study. Setting & Participants 28,678 patients with chronic kidney disease (CKD) stages 3 and 4 (estimated glomerular filtration rate [eGFR], 15–59 ml/min/1.73 m2) were identified using the Cleveland Clinic Chronic Kidney Disease Registry. CKD was defined as two eGFR values <60 ml/min/1.73 m2 drawn >90 days apart using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…The main action of this enzyme is to catalyze the hydrolysis of the calcification inhibitor pyrophosphate. 1 Pivotal studies conducted in dialysis 2,3 and in end-stage renal disease patients [4][5][6] demonstrated that ALP is linearly associated with all-cause and cardiovascular mortality, similarly to what also observed in patients without overt chronic kidney disease (CKD) 7,8 ; in addition, a significant association between serum ALP and coronary heart disease and total mortality has been previously reported in older men. 9 Recent data showed that mild inflammation and oxidative stress signaling play a key pathogenetic role in the development of vascular mineral deposition of which ALP is a wellestablished marker.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…The main action of this enzyme is to catalyze the hydrolysis of the calcification inhibitor pyrophosphate. 1 Pivotal studies conducted in dialysis 2,3 and in end-stage renal disease patients [4][5][6] demonstrated that ALP is linearly associated with all-cause and cardiovascular mortality, similarly to what also observed in patients without overt chronic kidney disease (CKD) 7,8 ; in addition, a significant association between serum ALP and coronary heart disease and total mortality has been previously reported in older men. 9 Recent data showed that mild inflammation and oxidative stress signaling play a key pathogenetic role in the development of vascular mineral deposition of which ALP is a wellestablished marker.…”
mentioning
confidence: 55%
“…by guest on May 10, 2018 http://hyper.ahajournals.org/ Downloaded from studies linking this molecule with mortality and cardiovascular events in patients with [4][5][6] or without 7,8 CKD. Taken together, our data are particularly relevant because they demonstrate, for the first time, a significant association between ALP and endothelial dysfunction, an early functional alteration in the continuum of vascular aging and atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Beddhu et al (2) reported that doubling baseline ALP level was associated with a 55% increase in all-cause mortality rate by a post hoc analysis from the African-American Study of Kidney Disease and Hypertension database. Another study including 28,678 patients with CKD stages 3 and 4 found that each 1-SD (42.7 U/L) higher ALP level was associated with 15% and 16% higher risk of ESRD and mortality, respectively, after multivariate adjustment (4). Some studies have examined the association between ALP level and mortality in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the National Health and Nutrition Examination Survey (NHANES) database show a graded independent association between higher ALP levels and mortality in the general population (1). In nondialysis-dependent CKD patients, higher ALP levels were associated with higher risk of ESRD and all-cause mortality (2)(3)(4). Similarly, in maintenance hemodialysis (HD) patients, elevated ALP levels were also associated with higher risk of mortality, independent of liver function and bone metabolism parameters (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic differences of the BALP isoforms with respect to PPi and other substrates, described by our group (71), suggest putative differences in the significance of the BALP isoforms for the process of vascular calcification. In CKD, numerous longitudinal and cross-sectional studies have demonstrated an association of ALP with mortality in different CKD populations (78, [173][174][175][176][177][178][179][180][181][182][183][184][185][186][187][188]. This association seems to be independent of PTH, phosphate, and calcium (174,176).…”
Section: The Role Of the Vascular Smooth Muscle Cell In Vascular Calcmentioning
confidence: 99%